Analysis of the Effectiveness of Instagram Social Media Content in Building Interest in Visiting Suruan Eco Park - Muhammad Addy Firmansyah; Aditya Rahman Yani; Masnuna Masnuna (Universitas Dian Nuswantoro, 2026)
In the current digital era, social media plays an important role in promoting tourism destinations as it enables rapid information dissemination and direct interaction with audiences through visual and narrative content. One of the platforms frequently used for tourism promotion is Instagram, as it has distinctive visual strengths that can shape perceptions and influence visit intentions. Suruan Eco Park is a nature-based tourism destination located in Tuban Regency that offers recreational experiences centered on natural landscapes and water-based activities. However, despite utilizing social media as a promotional tool, the number of tourist visits remains relatively low. This condition is presumed to be caused by the limited effectiveness of social media content management. This study aims to analyze the effectiveness of Instagram social media content of Suruan Eco Park in building prospective visitors’ intention to visit. The analysis focuses on content strategy, engagement level, and audience perception. The research employs a descriptive qualitative method with data collection techniques including observation of Instagram content, interviews with visitors, and the distribution of questionnaires through social media to obtain audience responses. The results indicate that Suruan Eco Park’s Instagram content is still dominated by one-way promotional communication and has not been supported by an effective and consistent visual communication strategy. Weak visual identity and destination image, limited narrative content, and the lack of strategic content evaluation result in the destination’s unique characteristics and advantages not being conveyed optimally. Although the existence of Suruan Eco Park has been introduced to the public, the persuasive power and engagement level of the content remain low, thus failing to significantly encourage visit intentions. This research is expected to contribute academically to the fields of Visual Communication Design and digital tourism, as well as serve as an evaluative reference and foundation for developing more effective and targeted visual communication strategies for Suruan Eco Park’s Instagram content. Keywords: social media, visit intention, nature tourism, Suruan Eco Park